Voluntary Diaspora and Missionary Purposes: Mapping Indonesian Muslim Diaspora in Western Countries - Ahmad Abrori; Eva Mushoffa; Dzuriyatun Toyibah (Journal of Asian Social Science Research, 2023)
This paper aims to show a new characteristic of diaspora. While previous literature discusses the issue of diaspora mostly in terms of victim subject and is associated with the marginalized individual and forced refugees, this article finds a new category which we call a voluntary diaspora. This term refers to a group of diaspora society who actively organize their members to maintain a social bond and identity. This finding was sufficiently generated by conducting literature research, especially on recent works of the diaspora of Indonesian Muslims in Western countries. The finding then contributes to the theoretical explanation of diaspora which is dominated by the notion that views diaspora as a victim phenomenon, as discussed in previous literature.